PENGARUH PERTUMBUHAN EKONOMI DAN BELANJA MODAL TERHADAP INDEKS KEPARAHAN KEMISKINAN DI PROVINSI JAMBI - Ahmad Soleh (Fakultas Ekonomi Universitas Prof. Dr. Hazairin, SH. Bengkulu, 2019)
The purpose of this study is to see and analyze the relationship and influence of economic growth and capital expenditure on the severity index of poverty in Jambi Province. The analytical approach used in this study is descriptive qualitative and quantitative using secondary data in the 2001-2015 tofu period obtained from BPS Jambi Province and the Directorate General of Fiscal Balance. While the analytical tool used in this study is multiple regression. The results showed that the variable economic growth and capital expenditure simultaneously had a positive and significant effect on the Poverty Severity Index. Likewise partially the variable of economic growth and capital expenditure does not affect the Severity Index of Poverty in Jambi Province.